Incidence and management of cystic duct perforation during endoscopic transpapillary gallbladder drainage for acute cholecystitis. Issue 1 (22nd March 2021) - Nakahara, Kazunari; Sato, Junya; Morita, Ryo; Michikawa, Yosuke; Suetani, Keigo; Igarashi, Yosuke; Sekine, Akihiro; Kobayashi, Shinjiro; Otsubo, Takehito; Itoh, Fumio
Abstract : Background and Aim: Evidence regarding the incidence and clinical outcome of cystic duct perforation (CDP) during endoscopic transpapillary gallbladder drainage (ETGBD) is inadequate. The present study aimed to evaluate the incidence and management of CDP during ETGBD. Methods: Between March 2011 and December 2019, 249 patients underwent initial ETGBD for acute cholecystitis. The incidence of CDP was retrospectively examined and the outcomes between the CDP and non‐CDP groups were compared. Results: CDP during ETGBD occurred in 23 (9.2%) of 249 patients (caused by guidewire in 15 and cannula in 8). ETGBD was successful in 10 patients following CDP. In 13 patients who failed ETGBD, 11 underwent bile duct drainage during the same session; nine patients underwent gallbladder decompression by other methods, such as percutaneous drainage. Clinical resolution for acute cholecystitis was achieved in 20 patients, and no bile peritonitis was noted. ETGBD technical success rates (45.3% vs. 91.2%, p < 0.001), ETGBD procedure times (66.5 vs. 54.8 min, p = 0.041), and hospitalization periods (24.5 vs. 18.7 days, p = 0.028) were significantly inferior in the CDP group ( n = 23) compared with the non‐CDP group ( n = 216). There were no differences in clinical success and adverse events other than CDP between both groups. Conclusions: Cystic duct perforation reduced the ETGBD technical success rate. However, even in patients with cystic duct perforation, an improvement of acute cholecystitis was achieved by subsequent successful ETGBD or additional procedures, such as percutaneous drainage.